RELATIONSHIP BETWEEN LEARNING OUTCOMES AND PEER ASSESSMENT PRACTICE - Adediwura, Adeyemi Alaba (European Scientific Journal, ESJ, 2015)
The study examined the effect of peer assessment on students’ mathematical retention ability and determined the effect of peer assessment practice on the students’ attitude towards mathematics learning. It also established the relationship between students’ attitude towards mathematics learning and peer assessment practice. These were with a view to improving students’ learning of mathematics. The population and the sample consisted of 45 private students in a remedial class who were preparing for Senior School Certificate Examination (SSCE) after an unsuccessful attempt at the end of their three years senior secondary school programme. Four instruments were employed for data collection. The instrument includes; Assessment Tasks (AT) used at the end of every mathematic teaching/learning process’, Students Attitudes towards Peer Assessment (SAPA) questionnaire, Students’ Attitude towards Mathematics (SAMS), Mathematics Post Training Test (MP2T) and a Mathematics Retention Test (MRT). The results showed that the peer assessment practice has a significant effect on the retention ability of the students (t = 1.83, df =44, p >.05) and (r = 0.97, p<.05). The results also showed that the effect of peer assessment practice on students’ attitude towards mathematics learning is significant (t = 11.46, df = 44, p <.05). Furthermore, the results showed that there is no significant relationship between students’ post training attitude towards mathematics and attitude towards peer assessment practice (r = - 0.064, p>.05). In conclusion peer assessment as adopted and use in this study may be said to be one of the possible alternatives assessment methods that will serve assessment formative functions and thus bring about improvement in students’ learning of mathematics